The air war against the Islamic State the role of airpower in Operation Inherent Resolve - Wasser, Becca; Pettyjohn, Stacie L.; Martini, Jeffrey; Evans, Alexandra T.; Mueller, Karl P.; Edenfield, Nathaniel; Tarini, Gabrielle; Haberman, Ryan; Zeman, Jalen (RAND Corporation, 2021)
Airpower played a pivotal role in the U.S.-led fight against the Islamic State in Iraq and Syria (ISIS) from 2014 to 2019 and contributed to the success of Operation Inherent Resolve. This report sheds light on the impact of the air operations in Operation Inherent Resolve and whether airpower could have been applied differently to achieve faster, more-sustainable outcomes. The authors incorporate interviews with U.S. and coalition personnel, primary-source documents, and U.S. and coalition strike and sortie data to document the operational history of the air war, assess the relationship between airpower effects, and analyze the strategic and operational impact of airpower in Operation Inherent Resolve. The authors find that, although airpower played an essential role in combating ISIS, airpower alone would not have been likely to defeat the militant organization. Instead, the combination of airpower and ground forces-led by Iraqi and Syrian partners-was needed to destroy the Islamic State as a territorial entity. The overarching strategy of Operation Inherent Resolve, which put ground-force partners in the lead, created several challenges and innovations in the application of airpower, which have implications for future air wars. To be prepared to meet future demands against nonstate and near-peer adversaries, the U.S. Air Force and the joint force should apply lessons learned from Operation Inherent Resolve
Keywords: IS (Organization); Air interdiction; Terrorism / Prevention / History / 21st century; Terrorism / Iraq / Prevention / International cooperation; Terrorism / Syria / Prevention / International cooperation